Designing a Zn(BF4)2‐Based Ionic Liquid Electrolyte to Realize Superior Energy Density in a Carbon‐Based Zinc‐Ion Hybrid Capacitor. Issue 7 (19th February 2021) - Zhang, Li; Wang, Gaowei; Feng, Jianze; Ma, Quanhu; Liu, Ziqiang; Yan, Xingbin
Abstract: Carbon‐based zinc‐ion hybrid capacitors (C‐ZIHCs), inheriting the merits from supercapacitors and batteries, exhibit promise in energy‐storage technologies. However, unsatisfactory energy density still hinders their practical applications for most reported C‐ZIHCs. We report a novel Zn(BF4 )2 /[EMIM]BF4 electrolyte to construct C‐ZIHCs with a high energy density. The Zn(BF4 )2 /[EMIM]BF4 electrolyte features high reductive/oxidative stability, which guarantees no significant dendrites and side reactions to corrode the Zn anode during the charging/discharging process, and achieves ultrafast Zn plating/stripping with a high coulombic efficiency (>99 %) and unprecedented cycling stability (over 1200 h). By virtue of the excellent properties of the electrolyte, C‐ZIHCs is built to exhibit a high average output voltage (1.9 V), a high energy/power density (220 Wh kg −1 /9.5 KW kg −1 ), and a long cycle life (95 % capacity retention after 20000 cycles). Herein, we report the use of Zn salt‐based ionic liquid as an electrolyte to construct C‐ZIHCs, which provides a new opportunity for the development of C‐ZIHCs with excellent comprehensive performance. Abstract : Zinc or swim : Based on the good compatibility between Zn(BF4 )2 /EMIMBF4 ionic liquid electrolyte, the Zn anode, and 3D‐AC cathode, the first application of this electrolyte is demonstrated to construct a carbon‐based zinc‐ion hybrid capacitor, which exhibits a high energy density (220 Wh kg −1 ) and long cycle life with good electrochemical stability (95 % capacity retention after 20.000 cycles).